Dramaturgi Pelaku Fraud Bertopeng Kebaikan dan Berselimut Dusta: Studi Kasus Dana Bencana Alam Organisasi Nirlaba - Rafles Ginting (University of Merdeka Malang, 2021)
The research is intended to reveal the meaning behind the practice of fraud in natural disaster funds in a non-profit organization, where the practice of fraud in a non-profit organization is not a foreign subject. The practice can be traced from every activity carried out. In the phenomenon that occurs in non-profit organizations, there are hidden practices behind and behind it can be found the causes of fraud. Dramaturgy theory is used in this study to reveal the activities of interaction with each other as well as the performance of a drama and prove a play of life presented by a handful of individuals and groups of people to seek attention. This study uses a qualitative method with a case study approach. The case study approach is considered very appropriate to be used in this study, because in this study it focuses on one case that occurred, namely the phenomenon of hidden practices in the form of masks of kindness and shrouded in lies behind the fraud of natural disaster relief funds in non-profit organizations. The data collection technique used observation, independent interview, and documentation study. The results of this study found the causes of hidden practices behind the fraud of natural disaster relief funds in organizations, where what is said to be the cause of these causes is a lack of supervision, a profit-seeking culture, the existence of opportunities or opportunities. the level of fraud in non-profit organizations which include; establishment of an internal audit team, regular supervision, establishment of anti-fraud policies, embedding the value of religiosity.